Estado, conflicto y reconciliación en Villahermosa, Medellín = State, Conflict and Reconciliation in Villahermosa, Medellín (2018)
Among the areas most affected by the armed conflict in Medellín is Comuna 8, also known as Villahermosa. Here, due to the presence of various armed actors, a particular relationship has developed between state institutions and civil society that has lasted until the present day, in what could be called the post-conflict stage. This paper seeks to explore this relationship and to give an account of one of the reconciliation experiences that have taken place in the territory and that has managed to meet needs that should initially be satisfied by the State through community work. For this purpose, it will approach the historical situation of the State in Villahermosa through the analysis of the natural catastrophe that occurred in 1987 and the consultation of bibliography on the State in Colombia; in addition, it will account for the experience of the Camposanto Corporation in Villatina through two interviews carried out with reinserted members of the AUC. The above in order, first, to understand the construction of the State in the country, which is far from the European experience and theory on the State and, second, to show citizen processes that can serve as references to solve public problems and to go through the current situation of disarmament and reinsertion of the FARC